Design And Development Of An Oil Palm Biomass Fluidized Bed Gasifier - Awaludin, Azali (2007)
Gasification demonstrates one of the cleanest and most efficient method to produce useful gases from low or negative-value carbon-based feedstock such as coal, petroleum coke and high sulfur fuel oil, It is a process that converts carbonaceous materials (e.g. oil palm biomass, wood etc) into carbon monoxide and hydrogen by reacting the raw material at high temperatures with a controlled amount of oxygen. An up draft fluidized bed gasifier using oil palm biomass as fuel has been designed and developed that is capable of producing a fuel flow rate of 20kg/hour, generating 10 kW (calculation) and output of 9 – 13 % or methane (CH4). The design was verified by simulation work on ANSYS 8.1 CFX 5.7 for the identification of material structure and dimensions. Stainless steel (SS 1040) was selected as material for the chamber because of its unique property of withstanding high operating temperatures of 700°C - 1400°C. Dimensions of gasifying chamber was selected at 1070 mm height with diameter of 200 mm, provided with supplementary two 4 kW air heater, air blower, thermocouple probes and cyclone and a fluidized bed of 900 mm depth. Refactory insulation was used to reduce heat loss to the environment. Initial investigation showed that a fuel of ratio 20% oil palm fibre - 80% oil palm shell was the most suitable mixture combination. Thus, fuel treatment is important to ensure complete gasification of oil palm biomass and the moisture content (mc) of the fuel is limited to 10-15% dry basis with of diameter of 5 mm and length of fibre the of 10mm. The results from simulation gave a predicted temperature of 984°C while an experimental result was 829°C. Analyses of component of synn gas produce using a gas-monitoring meter namely (Tempest Telegan), gas chromatography (Hewlett Packard) and for ash content composition using Atomic Absorbtion Spectrometer (AAS analysis). By-products of gasification were 345 ppm of NOx, 96 ppm of H2S, 31% of CO, 9-13% of CH4, 130 ppm of SO2, 56% of CO2 using gas monitoring and ash content were 52000 μg/g of iron, 241 μg/g of copper, 9 μg/g of lead, 120,000 μg/g of potassium, 7,846 μg/g of phosphorus and calorific value was detected at level 8.7 MJ with gas flow rate 6.93 m3/s. The gasifier has efficiency 50% to 75% of efficiency base on CV of gas components production for one hour operation. The gasifier developed using fluidized bed system fuelled with oil palm shells and fibres has great potential for producing renewable energy at palm oil mill when the synn gas is further purified.